POLA KOLABORASI SEKOLAH, GEREJA, DAN KELUARGA DALAM PRAKSIS PENDIDIKAN AGAMA KRISTEN - Ine Matongan; Yolanda; Sriyanti Pata' Lembang; Nia Yunita Bagenda (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
Collaboration among schools, churches, and families is frequently cited as a fundamental requirement for effective Christian Religious Education, yet existing studies remain largely normative in nature and lack a clear operational model, resulting in gaps between the three institutions when jointly carrying out the function of faith education. This study aims to analyze the pattern of collaboration among the three institutions in the praxis of Christian Religious Education, to analyze the gaps in their respective roles, and to analyze the factors influencing the effectiveness of such collaboration. A descriptive qualitative method with a library research approach was employed, examining biblical texts as primary sources and sixteen related journal articles as secondary sources through thematic content analysis. The findings indicate that the collaboration pattern found in the field tends to be situational and informational, not yet reaching the equal and collaborative form depicted in the metaphor of the body of Christ, thereby producing gaps in communication, curriculum, resources, and understanding of responsibility. Theological factors, leadership communication, socio-cultural context, and institutional structure were found to be the main determinants of collaborative effectiveness. This study affirms the need for a more operational collaborative model for schools, churches, and families in accompanying the growth of learners' faith.